Studi Kualitatif Pelaksanaan Pelayanan Swamedikasi di Apotek Bintang Farma - Nelli Purba; Rahmat Alyakin Dachi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Self-medication is self-medication that is usually done to treat mild health problems or disorders. The advantage of self-medication is that it is safe if the drug is used according to the rules, it is effective in dealing with it, it is cost-effective, it saves time, and it plays a role in making therapeutic decisions. On the other hand, the disadvantages of self-medication practice include being unsafe and even detrimental to the user if the prescribed medication rules are not complied with. The purpose of this study was to determine the implementation of self-medication services at the Bintang Farma Pharmacy, Lintongnihuta District, Humbang Hasundutan Regency. This type of research was a qualitative study. The main foundation of this research was design phenomenology with a qualitative approach. The informants in this study were eleven people consisting of key informants, main informants and additional informants. Subject selection was carried out using the snowball sampling method. Data was collected through in-depth interviews. Data analysis was carried out with three streams of activities that occurred simultaneously, namely data compaction, data presentation and conclusions (drawing and verification). The results of the analysis showed that the patient's knowledge about self-medication was still limited. Self-medication actions were generally carried out because of personal experience, family advice, the influence of advertising and promotion in the media. Self-medication was believed to be easy to do, fast, more cost-effective and time-effective. Rationality of drug use based on drug packaging labels related to drug indications, drug dosage, method of use and duration of drug use, method of drug storage and drug side effects. Standard operating procedures compiled by pharmacists become guidelines for providing self-medication services. Patient knowledge regarding self-medication services played a role in decision-making to take self-medication. The rationality of drug use was obtained from drug packaging. Standard operating procedures for self-medication were prepared by pharmacists and serve as guidelines for self-medication services. It was concluded that self-medication patients already know about self-medication from themselves, family, advertisements; with good rationality of instructions for using drugs and implementation of standard operating procedures from pharmacists.Keywords: self-medication; pharmacy; rationalization; knowledge ABSTRAK Swamedikasi adalah pengobatan sendiri yang biasanya dilakukan untuk mengatasi masalah kesehatan atau gangguan yang ringan. Keuntungan swamedikasi adalah aman apabila obat digunakan sesuai aturan, efektif mengatasi, hemat biaya, hemat waktu, dan berperan dalam pengambilan keputusan terapi. Sebaliknya, kerugian dari praktik swamedikasi antara lain bersifat tidak aman dan bahkan merugikan pemakai apabila aturan pengobatan yang seharusnya tidak dipatuhi. Tujuan penelitian ini adalah untuk mengetahui pelaksanaan pelayanan swamedikasi di Apotek Bintang Farma, Kecamatan Lintongnihuta, Kabupaten Humbang Hasundutan. Jenis penelitian ini adalah studi kualitatif. Landasan pokok penelitan ini adalah fenomenologi desain dengan pendekatan kualitatif. Informan dalam penelitian ini sebelas orang yang terdiri informan kunci, informan utama dan informan tambahan. Pemilihan subjek dilakukan dengan metode snowball sampling. Data dikumpulkan melalui wawancara mendalam. Analisis data dilakukan dengan tiga alur kegiatan yang terjadi secara bersamaan yaitu pemadatan data, penyajian data dan kesimpulan (gambaran dan verifikasi). Hasil analisis menunjukkan bahwa pengetahuan pasien tentang swamedikasi masih terbatas. Tindakan swamedikasi umumnya dilakukan karena pengalaman pribadi, saran keluarga, pengaruh iklan dan promosi di media. Swamedikasi diyakini mudah dilakukan, cepat, lebih hemat biaya dan waktu. Rasionalitas penggunaan obat berdasarkan etiket kemasan obat terkait indikasi obat, dosis obat, cara pemakaian dan lama pemakaian obat, cara penyimpanan obat dan efek samping obat. Standar operasional prosedur disusun oleh apoteker menjadi pedoman untuk memberikan pelayanan swamedikasi. Pengetahuan pasien terkait pelayanan swamedikasi berperan pada pengambilan keputusan untuk melakukan tindakan swamedikasi. Rasionalitas penggunaan obat diperoleh dari kemasan obat. Standar operasional prosedur swamedikasi disusun oleh apoteker dan menjadi pedoman pelayanan swamedikasi. Dismpulkan bahwa pasien swamedikasi sudah mengetahui swamedikasi dari diri pribadi, keluarga, iklan; dengan rasionalitas yang baik dari petunjuk penggunaan obat dan penerapan standar operasional prosedur dari apoteker.Kata kunci: swamedikasi; apotek; rasionalisasi; pengetahuan